Species identification and relationship of sea cucumber species from Pulau Tinggi and Sedili Kechil, Johor based on ossicle shape - Solehin, Siti Najihah; Kamarudin, Kamarul Rahim; Akashah, Nursyamfarhani; Mohamed Rehan, 'Aisyah; Abu Bakar, Muhammad Abdul Latiff; Badrulhisham, Nur Sabrina; Ab Rahman, Nor Shahida; Ummi Nurain Akma, .; Shahdan, Farhanah; Azman, Hanis; Mohd Fadzil, Siti Nursyuhada; Mohd Faid, Nurin Husnina; et al. (Penerbit UTHM, 2021)
Sea cucumbers are an abundant echinoderm group in Malaysia which provides commercial and medicinal values to local people. Due to the lack of data on sea cucumbers status in Johor coastal seawaters, this study was conducted. This study aimed to identify the species and relationship of sea cucumber from two selected Johor coastal seawater; Pulau Tinggi and Sedili Kechil based on ossicle shape. The current study recorded 53 individuals of sea cucumbers, of which 23 individuals were from Pulau Tinggi, Mersing District and 30 individuals were from Sedili Kechil, Kota Tinggi District. A number of 10 species of sea cucumber were found in the coastal waters of Pulau Tinggi, Mersing and three species in Sedili Kechil, Kota Tinggi, Johor. A total of 10 ossicle shapes were observed and extracted from the sea cucumber samples namely button, perforated plate, table, C-shaped rod, rosette, anchor, spider, I-shaped rod, boomerang, and J-shaped rod. The species relationship based on ossicle shapes was analysed using clustering option of PAST (PAleontological STatistics) software version 4.03. The analysis concluded that two groups of sea cucumber families i.e. Holothuriidae and Stichopodidae were present, although S. chloronotus clustered closer with the members of family Holothuriidae.. Although more specimens are required to generate better conclusive results, the outcomes provided updated data on sea cucumber species in Johor seawater.